2019
DOI: 10.3390/s19245548
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Monitoring with Distributed Mesh Networks: An Overview and Practical Implementation Perspective for Urban Scenario

Abstract: Almost inevitable climate change and increasing pollution levels around the world are the most significant drivers for the environmental monitoring evolution. Recent activities in the field of wireless sensor networks have made tremendous progress concerning conventional centralized sensor networks known for decades. However, most systems developed today still face challenges while estimating the trade-off between their flexibility and security. In this work, we provide an overview of the environmental monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
9
0
1
Order By: Relevance
“…The dramatically booming requirement of wireless sensor networks (WSN) demand more sensor nodes with sensing ability for different applications, such as ecological monitoring, health surveillance, and traffic control [ 1 , 2 , 3 , 4 ]. To ensure the stability of a reception link from plenty of the sensor nodes, high-performance antennas with high gains, orthogonal polarizations, and omnidirectional coverage are required in sink nodes.…”
Section: Introductionmentioning
confidence: 99%
“…The dramatically booming requirement of wireless sensor networks (WSN) demand more sensor nodes with sensing ability for different applications, such as ecological monitoring, health surveillance, and traffic control [ 1 , 2 , 3 , 4 ]. To ensure the stability of a reception link from plenty of the sensor nodes, high-performance antennas with high gains, orthogonal polarizations, and omnidirectional coverage are required in sink nodes.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques can be very accurate but require the use of bulky, power-hungry, and expensive instruments [ 19 , 20 ]. Thus, these approaches do not provide a scalable solution for monitoring with enough spatial resolution air pollution events related to automotive combustion or burning fuels for cooking in urban scenarios [ 20 , 21 , 22 , 23 ]. Furthermore, these technologies demand trained personnel to operate with complex equipment and, obviously, they cannot be implemented in portable, low-cost, and low-power devices.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, several authors have reported the use of Wireless Sensor Networks (WSNs) for air quality monitoring systems [ 20 , 22 ]. In that sense, some decision-making systems have been designed using both Local Area Networks (LANs) for the monitoring of local air quality or generating an alarm while under a gas pollution event [ 35 , 36 ] and Wide Area Networks (WANs) for remote control and monitoring [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In IIoT, a large number of sensors are used to periodically detect changes in machine health, manufacturing process, industrial environment, etc. [5][6][7][8][9][10]. Hence, a huge amount of data is collected from the sensors used in IIoT.…”
Section: Introductionmentioning
confidence: 99%